Calibration of hydrological models considering process interdependence: A case study of SWAT model. (October 2021) - Rajat,; Athira, P.
Abstract: Calibration is an essential step that is involved in the application of process based distributed hydrological models. The calibration process focuses on improving the performance index values rather than improving the process dynamics. The poor process dynamics in the model reduces its predictive power. The current study proposes a modified calibration approach (MCA) for the Soil and Water Assessment Tool (SWAT) model, which helps to improve the process dynamics in model through constraining the parameters. The modified calibration method uses the association between physically interpretable SWAT model parameters as soft data for calibration. The proposed calibration approach is validated in the Little River Experimental Watershed, USA. The results indicate that the proposed calibration method improves the process representation and spatial prediction in the calibrated model compared to the standard calibration procedure based on streamflow data. Graphical abstract: Comparison of Modified Calibration Approach(MCA) and Standard Calibration Approach(SCA) in terms of streamflow and soil moisture prediction at the watershed outlet for Case I (2006–2011) and Case II (2012–2016). Image 1 Highlights: The modified calibration approach has resulted in an improved simulation of both streamflow and soil moisture. Association between the physically interpretable SWAT model parameters are used as soft data for calibration. The modified calibration approach has resulted in an improved spatial prediction in SWAT. The proposed approach improves the process representation in calibrated model.